(untitled) (Вісник: Міжнародні відносини, 2024)
The author made an attempt to comprehensively analyze the impact of the Russian-Ukrainian war on the geopolitical situation in the South Caucasus region. The evolution of the Armenian-Azerbaijani conflict in Nagorno-Karabakh and its impact on the changing geopolitical environment in the South Caucasus region are considered. The reasons for the interest of global and regional international actors (USA, China, Russia, EU, UK, Turkey, Kazakhstan) in deepening cooperation with the states of the South Caucasus are analyzed.